The effect of nile tilapia (Oreochromis niloticus) protein concentrate fortification on sweet bread - Rinda Rinda Defira (Universitas Djuanda, 2019)
This study aimed to determine the best of protein concentrate fortification of nile tilapia (Oreochromis niloticus) on sweet bread. The treatment given consists of K0 (without fortification of fish protein concentrate), K1 (5% of fish protein concentrate fortification), K2 (10% of fish protein concentrate fortification), K3 (15% of fish protein concentrate fortification). The parameters analyzed in this study were sensory, physical and chemical analysis. The results showed that tilapia protein concentrate fortification had a significant effect on the sensory (organoleptic) value, physical analysis (volume development test) and chemical analysis (moisture, protein, fat, and carbohydrate content), but did not significantly affect on ash content. The best treatment was K1 (5% of fish protein concentrate fortification) with an average number of panelists who liked 77 people (96.25%), with the characteristics of bread which included appearance (brownish yellow and there were a few brown spots), aroma (typical of bread), texture (soft, elastis and good), taste (sweet) with development volume, moisture, ash, protein, fat, and carbohydrate content was 81.55%, 28.71%, 1.21%, 14.93%, 9.35%, and 45.80%, respectively.